TETRASPANIN 8-1 from Phaseolus vulgaris plays a key role during mutualistic interactions - Parra-Aguilar, Thelma J.; Sarmiento-López, Luis G.; Santana, Olivia; Olivares, Juan Elías; Pascual-Morales, Edgar; Jiménez-Jiménez, Saul; Quero-Hostos, Andrea; Palacios-Martínez, Janet; Chávez-Martínez, Ana I.; Cárdenas, Luis (Frontiers in Plant Science, 2023)
Arbuscular mycorrhizal (AM) fungi and rhizobia form two of the most important plant-microbe associations for the assimilation of phosphorus (P) and nitrogen (N). Symbiont-derived signals are able to coordinate the infection process by triggering multiple responses in the plant root, such as calcium influxes and oscillations, increased reactive oxygen species (ROS), cytoskeletal rearrangements and altered gene expression. An examination was made of the role of tetraspanins, which are transmembrane proteins that self-organize into tetraspanin web regions, where they recruit specific proteins into platforms required for signal transduction, membrane fusion, cell trafficking, and ROS generation. In plant cells, tetraspanins are scaffolding proteins associated with root radial patterning, biotic and abiotic stress responses, cell fate determination, plasmodesmata and hormonal regulation. Some plant tetraspanins, such as Arabidopsis thaliana TETRASPANIN 8 and TETRASPANIN 9 (AtTET8 and AtTET9) are associated with exosomes during inter-kingdom communication. In this study, a homolog of AtTET8, PvTET8-1, in common bean (Phaseolus vulgaris L. var. Negro Jamapa) was examined in roots during interactions with Rhizobium tropici and Rhizophagus irregularis. The promoter of PvTET8-1 contained several cis-acting regulatory DNA elements potentially related to mutualistic interactions, and PvTET8-1 was transcriptionally activated during AM fungal and rhizobial associations. Silencing it decreased the size and number of nodules, nitrogen fixation, and mycorrhizal arbuscule formation, whereas overexpressing it increased the size and number of nodules, and mycorrhizal arbuscule formation but decreased nitrogen fixation. PvTET8-1 appears to be an important element in both of these mutualistic interactions, perhaps through its interaction with NADPH oxidase and the generation of ROS during the infection processes.